2006
DOI: 10.4319/lo.2006.51.6.2711
|View full text |Cite
|
Sign up to set email alerts
|

Primary production in two shallow lakes with contrasting plant form dominance: A paradox of enrichment?

Abstract: We estimated total lake plant biomass and primary net production in two shallow Swedish lakes that differ in nutrient loading and plant form dominance. In clearwater Lake Krankesjö n (10 mg chlorophyll a L 21 ), submerged macrophytes contributed more than phytoplankton and epiphyton to the estimated plant biomass. Estimated net primary production during May to September was 90-130, 1.2, and 14 g C m 22 for phytoplankton, epiphyton, and submerged macrophytes, respectively. In turbid Lake Bö rringesjö n (60-80 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 50 publications
4
48
0
Order By: Relevance
“…However, the degree to which these broad differences can be attributed to changes in corresponding regime shifts as opposed to changes in nutrient availability is difficult to say. This is especially the case with shallow lakes, as studies by Vadeboncoeur et al (2008) and Blindow et al (2006) have shown that a loss of benthic primary production with eutrophication may be anticipated with a shift from a clear-water to a turbid regime, potentially outweighing the positive effects of eutrophication on pelagic primary production. In such instances, a decline in heterotrophy following a shift to phytoplankton dominance would not, theoretically, result from an increase in whole-lake primary production, but rather from a decrease in respiration (i.e., C mineralization) rates.…”
Section: Introductionmentioning
confidence: 99%
“…However, the degree to which these broad differences can be attributed to changes in corresponding regime shifts as opposed to changes in nutrient availability is difficult to say. This is especially the case with shallow lakes, as studies by Vadeboncoeur et al (2008) and Blindow et al (2006) have shown that a loss of benthic primary production with eutrophication may be anticipated with a shift from a clear-water to a turbid regime, potentially outweighing the positive effects of eutrophication on pelagic primary production. In such instances, a decline in heterotrophy following a shift to phytoplankton dominance would not, theoretically, result from an increase in whole-lake primary production, but rather from a decrease in respiration (i.e., C mineralization) rates.…”
Section: Introductionmentioning
confidence: 99%
“…The diatom record shows that as water clarity improved and diatom production increased, the community that was established around 1978 persisted into the clear-water state. Within the cyanobacterial community, however, large changes occurred in 1988, when small, noncolonial cyanobacteria were replaced by colonial, toxic Microcystis botrys and M. aeruginosa, as well as by the golden alga Dinobryon sociale (Blindow et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…By 1948, the submerged vegetation had recovered in Lake Krankesjön, and in the 1950s and 1960s submerged vegetation was well developed (Karlsson et al 1976). A shift to the turbid state occurred in the mid-1970s, and the lake had sparse submerged vegetation for almost a decade (Blindow et al 2006). In the mid-1980s, submerged vegetation rapidly started to recolonize the lake, and since the late 1980s, the lake has been in a clear-water state, with abundant macrophyte beds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Submerged macrophytes, which are the main aquatic primary producers, act as indicators of the ecological quality of freshwater ecosystems because they can improve water transparency, purify water quality, and maintain water biodiversity [1][2].…”
Section: Introductionmentioning
confidence: 99%